Індивідуальна мінливість репродуктивних органів у Cupressus sempervirens L., С. arizonica Greene, С. lusitaica Mill. та С. macrocarpa Hartv. у культурі на півдні СНД - Zakharenko, G.S. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2002)
It is shown that according to the level of individual variability of 6 morphological characteristics of seeds cones and number of microsporophylls in microstrobils, the reproductive total combinations of mass propagated cypresses evergreen and c. arizona in the Crimea and cypress lusitanica on the Black Sea Coast of the Caucasus are maximum close to natural populations. The conclusion that the reproductive total combinations of the species, presented by 20 generations of seed local reproduction, are regarded as integrative introduction population from the microevolution point of view have been done. The data about frequency of growing of cypress evergreen with different form of scales and size of cones on the South Coast of the Crimea have been given according to the scales forms three types of phenovariations have been determined. The abnormal microstrobils with spiral microsporophylles of some cypress evergreen is considered to be the development of ancestor's characteristic usual for Taxodiaceae group, from which the cypresses comes.